2003
DOI: 10.1111/1469-7610.00204
|View full text |Cite
|
Sign up to set email alerts
|

Exploring selective attention in ADHD: visual search through space and time

Abstract: Children with ADHD were not impaired in their mechanisms of visual search relative to controls, but their error patterns implied the adoption of a premature response deadline in the conjunction search condition, and an occasional failure to inhibit old items in the preview condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
67
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 47 publications
(83 reference statements)
10
67
2
1
Order By: Relevance
“…Furthermore, our finding is consistent with recent work that has also failed to find a specific ADHD deficit in selective attention. 88,89 Contrary to our hypothesis, we found no evidence of an association between the DAT1 10/10 genotype and performance on working memory measures (irrespective of the subcomponent) and on a measure of sustained attention. Performance on the latter task was predicted only by high ADHD scores.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, our finding is consistent with recent work that has also failed to find a specific ADHD deficit in selective attention. 88,89 Contrary to our hypothesis, we found no evidence of an association between the DAT1 10/10 genotype and performance on working memory measures (irrespective of the subcomponent) and on a measure of sustained attention. Performance on the latter task was predicted only by high ADHD scores.…”
Section: Discussioncontrasting
confidence: 99%
“…A target defined on the basis of a conjunction of features relative to distractors (e.g., shape and color) tends to be harder to detect by identifying just one feature, as reaction times (RTs) slow down in a linear fashion indicating an increase in the number of distractors. Conjunction search depends on attention-demanding serial-search processes (Treisman & Gelade, 1980) and can be an adequate measure for selective attention (Mason, Humphreys, & Kent, 2003).…”
mentioning
confidence: 99%
“…Moreover, these results have been mixed. For example, two studies found that children with ADHD were overall slower and made more errors but did not show differences in RT and accuracy (ACC) as a function of an increased number of distractors (the slope used to assess selective attention) compared to controls (Hazell et al, 1999;Mason et al, 2003). In contrast, some studies using the conjunctive visual-search task did find poorer search performance in children with ADHD compared to comparison controls (Booth et al, 2005;Mullane & Klein, 2008;Shalev & Tsal, 2003;Tsal, Shalev, & Mevorach, 2005).…”
mentioning
confidence: 99%
“…A selective attention deficit corresponds to difficulties in focusing on a relevant target while ignoring irrelevant information. Even though this topic has been hotly debated (for a review, see Wilding, 2005), previous research has indicated that children with ADHD suffer from sustained attention deficits more than they do from spatial selective attention deficits (Booth et al, 2005;Hazell et al, 1999;Karatekin & Asarnow, 1998;Mason, Humphreys, & Kent, 2003;Tsal, Shalev, & Mevorach, 2005;Van der Meere & Sergeant, 1988). Spatial selective attention has been studied through the application of visual search paradigms, in which participants are asked to detect the presence of a target among simultaneously presented distractors (Treisman & Gelade, 1980;Wolfe, 1998).…”
Section: Temporal Selective Attention Deficits In Adhdmentioning
confidence: 99%